(untitled) (Marketing Journal, 2025)
The article studies the role of small business and private entrepreneurship in the economy, measures being taken to develop small business and private entrepreneurship in our country. The population employed in small business and private entrepreneurship i n Namangan region and business entities by type of economic activity in the region are analyzed. Proposals and recommendations are made for the further development of entrepreneurship in Namangan region.